2019
DOI: 10.1007/s13770-019-00192-0
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Printed Mg-Doped β-TCP Bone Tissue Engineering Scaffolds: Effects of Magnesium Ion Concentration on Osteogenesis and Angiogenesis In Vitro

Abstract: BACKGROUND: Three-dimensional (3D) printed bone tissue engineering scaffolds have been widely used in research and clinical applications. b-TCP is a biomaterial commonly used in bone tissue engineering to treat bone defects, and its multifunctionality can be achieved by co-doping different metal ions. Magnesium doping in biomaterials has been shown to alter physicochemical properties of cells and enhance osteogenesis. METHODS: A series of Mg-doped TCP scaffolds were manufactured by using cryogenic 3D printing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 56 publications
4
96
0
1
Order By: Relevance
“…Unlike copper or strontium, magnesium was much more often incorporated within metallic materials [69,75,83,106,107] rather than in bioglasses or bioceramics. [108] The response of ECs to the magnesium-containing materials varied and greatly depended on the concentration. Several studies showed improvement in angiogenic capacity in terms of proliferation, migration, tube formation, and expression of angiogenic genes, after introducing the culture to magnesium.…”
Section: Magnesiummentioning
confidence: 99%
“…Unlike copper or strontium, magnesium was much more often incorporated within metallic materials [69,75,83,106,107] rather than in bioglasses or bioceramics. [108] The response of ECs to the magnesium-containing materials varied and greatly depended on the concentration. Several studies showed improvement in angiogenic capacity in terms of proliferation, migration, tube formation, and expression of angiogenic genes, after introducing the culture to magnesium.…”
Section: Magnesiummentioning
confidence: 99%
“…The same kind of scaffolds was also used by Gu and colleagues. This group investigated the effect of magnesium ion concentrations on osteogenesis and angiogenesis of BM-MSC and HUVEC in 3D printed scaffolds in vitro [37]. Bone regeneration with membranes is a very new strategy, which was investigated by the group of Ye.…”
Section: Angiogenesis In Bone Transplantsmentioning
confidence: 99%
“…In recent years, to obtain suitable orthopedic biomaterials to allow the full healing of bone defects before their complete degradation, studies have been carried out to combine magnesium-based materials with diverse biodegradable and biocompatible three dimensional (3D) porous scaffolds [1,[4][5][6][12][13][14][15][16][17][18][19][20][21][22]. Scaffolds are supporting structural devices that can influence the behavior of cells in bone tissue regeneration processes [17,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, scaffolds should be characterized by a surface chemistry suitable for cell attachment, proliferation, and differentiation, as well as the presence of mechanical properties matching those of the tissues at the site of implantation [23][24][25]27]. Thus, different typologies of magnesium-containing scaffolds were studied for bone tissue engineering: β-tricalcium phosphate (β-TCP) scaffolds decorated with gelatine containing magnesium [12]; scaffolds produced by freeze-drying [4], viscous mass foaming [5], cryogenic 3D printing, or sintering in the presence of magnesium-containing powders [13]; poly(lactic-co-glycolic acid) (PLGA)/TCP/magnesium scaffolds made by low-temperature rapid prototyping [1]; alginate scaffolds that incorporate bioactive glass particles containing Zn and Mg [14]; bioactive glass-based scaffolds coated with hydroxyapatite (HA) loaded with Mg and Zn [6]; and gelatine-, chitosan-, and magnesium-enriched montmorillonite scaffolds [15]. The use of a polymeric matrix is generally proposed as a solution to improve the mechanical properties of scaffolds.…”
Section: Introductionmentioning
confidence: 99%